Striking the Balance: How Workplace Flexibility Enhances Engagement and Performance of Employees working in Public and Private settings - Parveen, Musrrat; Rizq, Abrar Talal (Zielona Góra: Faculty of Economics and Management Press)
This study investigates the relationships between workplace flexibility, employee engagement, and performance of employees working in public and private settings. The purpose is to understand how flexible work arrangements influence employee engagement and overall performance across various industries. This research was conducted using a descriptive quantitative method. A structured questionnaire was used to collect data from 400 employees across finance, technology, healthcare, and manufacturing industries.
Keywords: workplace flexibility; PLS (SEM); private organizations; employee engagement; employee performance